Other subjects, other school? Strategies and practices in the context of specific schools for the deaf - Liane Camatti; Márcia Lise Lunardi-Lazzarin (Universidade Federal de Santa Maria (UFSM), 2011)
The deaf community has recursively searched for specific schools for the deaf because it is a space where you could find safety and resistance conditions. Through this article, it seeks to understand how the assumptions that support the school institution are directed, given the nearness with the movements for the deaf. To accomplish this approach, we used excerpts from interviews with deaf, teachers and students from different specifically schools for the deaf of the State of Rio Grande do Sul. The studies of the post-structuralist concern provided the theoretical tools that enabled the analysis. Through this research, it became clear how the deaf community falls within the school, making the assumptions of cultural capital legitimized in the school for the deaf. Nevertheless, it was possible to look at how the processes of discipline inherent in the educational institution happen the same way in the school for the deaf, even though it was taken by the deaf as the site of redemption and as its largest trench.